Analysis of the effectiveness of physical rehabilitation according spirographic indicators in community-acquired pneumonia during convalescence - Kalmykova, Y. S.; Yurko, N. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to make a program of physical rehabilitation for convalescents after community-acquired pneumonia, promotes normalization of respiratory function. The objectives of the study was to evaluate the dynamics spirographic indicators during convalescence community-acquired pneumonia. Material: the study involved 28 women aged 19 to 24 years with a diagnosis of community-acquired pneumonia after convalescent. Results: the positive influence of physiotherapy based dance aerobics; morning hygienic gymnastics; therapeutic massage and physical therapy on indicators of lung volumes, ventilation and bronchial patency according spirographic research. Conclusion: in community-acquired pneumonia during the convalescence period recommended physical rehabilitation, which includes curative gymnastics based on dance aerobics, morning hygienic gymnastics, massage therapy, physiotherapy. It improves the functionality of the cardiorespiratory system, nonspecific immunity and overall physical performance level.